(untitled) (International Journal of Multidisciplinary Perspectives in Higher Education, 2020)
College and career readiness is a focal area within the United States for student achievement within the context of global competitiveness. Despite recent efforts to focus on the college and career readiness of America’s students, national data has proven that many students are not prepared for college and need remedial intervention upon entrance into college. This discussion focuses on efforts at community colleges, specifically in the area of literacy, as they work to increase student retention and student success. Recent methods include developmental courses, co-requisite models, and statewide initiatives to determine how to best meet students’ academic needs, while considering faculty voice and administrative and cost efficiency. Community colleges can serve as grounds to determine how various models of remediation work to ensure that college students can be served in the best capacity for their academic needs, excel in their programs of choice, and in turn, be competitive global citizens.